Age-dependent interactions of APOE isoform 4 and Alzheimer’s disease neuropathology: findings from the NACC - Cellas A. Hayes; Roland J. Thorpe; Michelle C. Odden (Acta Neuropathologica Communications)
Abstract Alzheimer’s disease related pathologies, neurodegenerative pathologies, and vascular neuropathologies are common in older adults at death. Previous studies using the National Alzheimer’s Coordinating Center (NACC) have not investigated the association between age at death and apolipoprotein E (APOE) ε4 and the prevalence of neuropathologies found at autopsy. We used autopsy confirmed neuropathology data from the NACC to examine the interactive effects of age and APOE ε4 on various neuropathologies (N = 5,843) using modified Poisson regression to estimate the prevalence ratios. Significant interactions between APOE ε4 and age at death were observed for neuritic plaques, Braak staging, diffuse neuritic plaques, and Lewy body disease pathology, with the effect of APOE ε4 decreasing at older ages. In contrast, a significant positive interaction was found for hemorrhages/microbleeds, indicating that the association between APOE ε4 and microbleeds strengthens with increasing age. These findings suggest that future therapeutic strategies should consider both genetic risk and age to effectively target AD progression.